Donor Lungs’ Procurement Implementation with Ex Vivo Lung Perfusion in a Low-Volume Lung Transplant Center - Matteo Petroncini; Elena Salvaterra; Leonardo Valentini; Silvia Bonucchi; Niccolò Daddi; Saverio Pastore; Pietro Bertoglio; Piergiorgio Solli; Filippo Antonacci (Life)
(1) Background: Ex Vivo Lung Perfusion (EVLP) is a technique designed to assess and recondition marginal lungs, potentially expanding the donor pool and improving transplant outcomes (2) Methods: This retrospective study evaluated lung transplantation outcomes after EVLP. Donor lungs were assessed using the Toronto protocol, with data on hemodynamics, gas exchange, and perfusion parameters collected and analyzed. Post-transplant complications and survival rates were also examined. (3) Results: Over five years, 17 EVLP procedures were performed. Despite an improvement in lung function, 47% of donor lungs were rejected after EVLP. EVLP-reconditioned lungs showed comparable survival rates to standard transplants, but complications like sepsis and primary graft dysfunction (PGD) occurred. (4) Conclusions: EVLP shows promise in expanding the donor organ availability and reducing PGD, but nearly half of the lungs assessed were rejected. Further research is necessary to optimize EVLP and address potential complications like lung injury and sepsis.